Protocatechuic acid attenuates isoproterenol-induced cardiac hypertrophy via downregulation of ROCK1–Sp1–PKCγ axis - Liyan Bai; Hae Jin Kee; Xiongyi Han; Tingwei Zhao; Seung-Jung Kee; Myung Ho Jeong (Scientific Reports, 2021)
Abstract Cardiac hypertrophy is an adaptive response of the myocardium to pressure overload or adrenergic agonists. Here, we investigated the protective effects and the regulatory mechanism of protocatechuic acid, a phenolic compound, using a mouse model of isoproterenol-induced cardiac hypertrophy. Our results demonstrated that protocatechuic acid treatment significantly downregulated the expression of cardiac hypertrophic markers (Nppa, Nppb, and Myh7), cardiomyocyte size, heart weight to body weight ratio, cross-sectional area, and thickness of left ventricular septum and posterior wall. This treatment also reduced the expression of isoproterenol-induced ROCK1, Sp1, and PKCγ both in vivo and in vitro. To investigate the mechanism, we performed knockdown and overexpression experiments. The knockdown of ROCK1, Sp1, or PKCγ decreased the isoproterenol-induced cell area and the expression of hypertrophic markers, while the overexpression of Sp1 or PKCγ increased the levels of hypertrophic markers. Protocatechuic acid treatment reversed these effects. Interestingly, the overexpression of Sp1 increased cell area and induced PKCγ expression. Furthermore, experiments using transcription inhibitor actinomycin D showed that ROCK1 and Sp1 suppression by protocatechuic acid was not regulated at the transcriptional level. Our results indicate that protocatechuic acid acts via the ROCK1/Sp1/PKCγ axis and therefore has promising therapeutic potential as a treatment for cardiac hypertrophy.